MESH REGULATION IN BACKWATER PRAWN FISHING GEAR. - GEORGE, V C; NAYAR, S GOPALAN; IYER, H KRISHNA (Fishery Technology, 2017)
Size grade composition of d1tlerent species of prawn caught by various back water fishing gear have been enumerated. 57 to 75% of P. indicus captured was less than 10 em. in length. 111. dobsoni and M. monoceros captured (were less than 10 em. in length. A cod end mesh size of 20-25 mm. has been recomended for stake nets for the capture of P. indicus of 10 em. length along with other species.